2011
DOI: 10.1007/s12603-011-0097-2
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of antioxidant supplementation and resistance training on oxidative stress markers, muscle and body composition in an elderly population

Abstract: This study was aimed to examine the effect of vitamin C/E intake alone or combined with resistance training on antioxidant/pro-oxidant status, muscle strength and body composition in an elderly population. Fifty-seven men and women with a mean age of 65.6 ± 3.8 years were recruited and randomized in a double-blind fashion into four groups: control-placebo; resistance training (RT); vitamins C/E supplementation (AS); AS+RT. Oxidative stress status and metabolic and lipid profiles were determined at baseline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 57 publications
1
60
2
Order By: Relevance
“…Other studies have not found an effect of resistance training on other markers of free-radical damage. For example, a study by Bobeuf et al [144] did not detect any differences in plasma MDA and urinary F 2 -isoprostane levels between before and after resistance training in older adults. The differences in these studies' results may be related to the choice of markers of free-radical damage, as well as the measuring compartments (blood, muscle, plasma).…”
Section: Oxidative Stress and Resistance Training In Elderly Peoplementioning
confidence: 92%
“…Other studies have not found an effect of resistance training on other markers of free-radical damage. For example, a study by Bobeuf et al [144] did not detect any differences in plasma MDA and urinary F 2 -isoprostane levels between before and after resistance training in older adults. The differences in these studies' results may be related to the choice of markers of free-radical damage, as well as the measuring compartments (blood, muscle, plasma).…”
Section: Oxidative Stress and Resistance Training In Elderly Peoplementioning
confidence: 92%
“…Only three human training studies have applied a high-force, resistance mode of exercise; i.e., traditional strength training [23,24] and eccentric exercise [25]. In a study by Theodorou et al [25], no effects of vitamin C and E supplementation (1000 mg and 400 IU, respectively) were found on either recovery after eccentric exercise or adaptation to 4 weeks of eccentric training.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-oxidant supplementation was not associated with any improvements in blood markers of recovery, perceived muscle soreness, or muscle function. Similarly, no difference in strength gains with vitamin C and E supplementation compared to placebo occurred after 6 months of resistance training in older adults [18]. Antioxidant supplementation may blunt the endogenous adaptive responses to exercise-induced oxidative stress such as improvements in insulin sensitivity [20].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant supplementation may blunt the endogenous adaptive responses to exercise-induced oxidative stress such as improvements in insulin sensitivity [20]. The consequences of these effects remain unclear, yet the limited data demonstrate no ergogenic benefit associated with antioxidant supplementation during resistance training [17,18]. …”
Section: Discussionmentioning
confidence: 99%